Perspective on Sleep and Aging - Monjan, Andrew A. (Frontiers in Neurology, 2010)
There is a strong body of data directly interrelating sleep problems with mood disorders. There is a growing data base directly associating sleep disorders with attention and memory problems. Motor disorders, especially involving the dopaminergic system, may produce sleep problems, including a possible association between disordered sleep and nocturnal falls. Sleep disorders may be causal conditions for metabolic diseases and increased risk for morbidity and mortality. Sleep and health are directly interrelated. To further probe these issues, especially as related to the aging process, investigators need to utilize tools and concepts from genomics and epigenetics, proteomics, metabolomics, any future ...omics, molecular neuroimaging, and cognitive neuroscience.